The Relationship between Social Support and Food Insecurity in Pregnant Women: A Cross-sectional Study - Nasibeh Sharifi; Mahrokh Dolatian; Zohreh Mahmoodi; Fatemeh Mohammadi Nasr Abadi; Yadolah Mehrabi (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Household food insecurity has increasingly been recognized as a serious public health problem which is associated with higher rates of self-reported poor or chronic health conditions and also adverse impact on the mother and foetus. Aim: The present study was aimed at identifying the relationship between social support and food insecurity in pregnant women. Materials and Methods: This cross-sectional study was carried out on 734 pregnant women using Stratified cluster sampling in Ilam province in 2016. Some urban health centers were selected from each city and the samples that had the inclusion criteria were enrolled in the study in their 24-28 gestational weeks. Data collection tools were four questionnaires; women’s demographic and obstetric characteristics, socio-economic status, food security status and social support questionnaires. Data were analysed using descriptive statistics and Chi-square test and logistic regression through SPSS version 19.0. The statistical tests were performed at 95% confidence interval. Results: Food security was observed in 64.9% of participants while 35.1% suffered from insecurity. The results of assessing social support status indicated that 15.4%, 50.4% and 34.2% of the pregnant women had low, moderate and high social support, respectively. The chi-square test showed that there was significant association between social support and food security (p<0.001). The results of the logistic regression analysis revealed that social support was a protective factor against food insecurity as the probability of household food insecurity was lower for women with a higher level of social support compared to those with lower social support (OR: 0.187, CI: 0.116-0.303). Conclusion: There was significant association between perceived social support and food insecurity. This highlighted the necessity of providing educational programs for spouses and families of pregnant women in order to support and alleviate food insecurity.